Polymer semiconductor shielding material, preparation method and semiconductor shielding layer

By adding modified carbon nanotubes to the polymer semiconductor shielding layer to replace part of the carbon black, the problem in the existing technology that it is difficult to improve the interface smoothness and conductive properties at the same time is solved, and the conductive properties and interface smoothness are significantly improved. Suitable for HV and EHV cables.

CN119331341APending Publication Date: 2025-01-21BEIJING BEIHUA GAOKE NEW TECH

Patent Information

Application Number
CN202411509583.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously improve the interface smoothness and conductivity of the polymer semiconductor shielding layer with carbon black added.

Method used

Modified carbon nanotubes are added to the raw materials of the existing polymer semiconductor shielding layer with carbon black added to replace part of the carbon black, thereby producing a polymer semiconductor shielding layer with good conductivity and high interface smoothness.

Benefits of technology

By using modified carbon nanotubes, the conductive performance and interface smoothness of the polymer semiconductor shielding layer are significantly improved, meeting the conductive performance and interface smoothness requirements of HV and EHV cables.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005105064290000051
    Figure BDA0005105064290000051
  • Figure BDA0005105064290000071
    Figure BDA0005105064290000071
  • Figure BDA0005105064290000151
    Figure BDA0005105064290000151
Patent Text Reader

Abstract

The invention relates to a shielding material for a high-voltage cable, in particular to a semiconductor shielding material, a semiconductor shielding layer and a preparation method of the semiconductor shielding layer. According to the invention, a certain amount of modified carbon nanotubes are added on the basis of the raw materials of the existing polymer semiconductor shielding layer added with carbon black, and the modified carbon nanotubes are used for replacing part of carbon black, so that the polymer semiconductor shielding layer with good conductivity and high interface smoothness is prepared. The surface of the modified carbon nanotube is grafted with organic silicon and a polar ethylene polymer, so that the dispersity of the modified carbon nanotube in a polymer semiconductor shielding material system and the compatibility of the modified carbon nanotube with the resin surface are improved; the viscosity of a polymer semiconductor shielding material system under high shear strength is greatly reduced, so that the flowability of the system is greatly improved; the semi-conductive shielding material which is suitable for HV and EHV cables and has super smoothness and strong conductivity is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a shielding material for high voltage cables, and more particularly to a polymer semiconductor shielding material, a preparation method and a semiconductor shielding layer. Background Art

[0002] The structure of medium voltage / high voltage / extra high voltage (MV / HV / EHV) cables usually includes a core (conductor), a first semiconductor shielding layer, an insulating layer, a second semiconductor shielding layer, a metal wire used as a grounding phase, and a protective sheath. The semiconductor shielding layer provides an intermediate resistivity layer between the high potential conductor and the main insulating layer and between the main insulating layer and the grounding or neutral potential layer. The semiconductor shielding layer is located between the conductor and the insulating layer in the power cable structure. It mainly plays the role of homogenizing the electric field distribution inside the insulating layer, eliminating the air gap between the conductor core and the insulating layer, and between the insulating layer and the outer conductive layer, thereby preventing partial discharge and improving the cable operation stability and cable service life. At present, polymer semiconductor shielding has been used in multi-layer power cable structures.

[0003] Polymer semiconductor shielding layers with ultra-high smoothness are required in HV and EHV cables. Improving the smoothness of the semiconductor shielding layer interface can achieve longer cable life, thereby minimizing local stress concentration. A common method for achieving an ultra-smooth interface between a semi-polymer conductor shielding layer and a conductor or insulating layer is to add carbon black, especially acetylene black, during the preparation of the semiconductor shielding layer. Due to the special physical and chemical properties of acetylene black, it has fewer surface defects and higher smoothness observable on the surface of the extruded product compared to furnace carbon black. The semiconductor shielding layer is usually extruded together with the insulating layer through a triple extrusion system. During the co-extrusion process of the semiconductor shielding layer added with carbon black, a weld line may occur at the interface of two shielding layer melts added with carbon black, and a protrusion between the semiconductor shielding layer and the insulating layer may be generated at the weld line position. That is, when the semiconductor shielding layer added with carbon black is prepared by a co-extrusion process, protrusions are easily generated, resulting in a decrease in the interface smoothness of the semiconductor shielding layer added with carbon black.

[0004] For the semiconductor shielding layer, in addition to meeting the interface smoothness requirements of HV and EHV cables, it is also necessary to meet the volume resistivity requirements of HV and EHV cables. Although adding carbon black during the preparation of the semiconductor shielding layer can reduce the volume resistivity of the polymer semiconductor shielding layer, its volume resistivity still needs to be further improved. Summary of the invention

[0005] The technical problem solved by the invention is how to simultaneously improve the interface smoothness and the conductive performance of a polymer semiconductor shielding layer added with carbon black.

[0006] The invention adds a certain amount of modified carbon nanotubes to the raw materials of the existing polymer semiconductor shielding layer added with carbon black, and replaces part of the carbon black with the modified carbon nanotubes, thereby preparing a polymer semiconductor shielding layer with good conductivity and high interface smoothness.

[0007] One of the purposes of the present invention is to provide a polymer semiconductor shielding material which can be used for high voltage cables.

[0008] A polymer semiconductor shielding material is prepared from raw materials comprising the following components;

[0009] Taking the total weight of raw materials as 100%, the components and their contents are as follows:

[0010] Ethylene polymer 40-80wt%, preferably 50-68wt%, more preferably 65-68wt%;

[0011] Carbon black 10-40wt%, preferably 30-38wt%, more preferably 30-36wt%, further preferably 30-34wt%;

[0012] 0.1-20wt% of modified carbon nanotubes, preferably 0.5-12wt%, more preferably 0.5-5wt%, further preferably 1-3.5wt%, for example 1.1wt%, 2.1wt%, 3.1wt%;

[0013] Peroxide 0-5wt%, preferably 0.5-2wt%;

[0014] Antioxidant 0-5wt%, preferably 0.1-1wt%.

[0015] The ethylene polymer is selected from one or more of a non-polar ethylene polymer and a polar ethylene polymer A. As a preferred embodiment, the ethylene polymer consists of a non-polar ethylene polymer and a polar ethylene polymer A; wherein the content of the polar ethylene polymer A is 1 to 60 wt%, preferably 20 to 60 wt%, more preferably 40 to 60 wt%, and further preferably 40 to 50 wt%.

[0016] The non-polar ethylene polymer is polymerized from ethylene, α-olefin and optional diene, wherein the content of the structural unit derived from α-olefin can be 1-25wt%, preferably 5-20wt%, the content of the structural unit derived from the optional diene is greater than 0 and ≤10wt%, preferably 3wt%, and the rest is the structural unit derived from ethylene.

[0017] The α-olefin is an α-olefin having 3 to 12 carbon atoms, preferably an α-olefin having 4 to 8 carbon atoms.

[0018] The non-polar ethylene polymer may be selected from high density polyethylene (HDPE), medium density polyethylene (MDPE), low density polyethylene (LDPE), very low density polyethylene (VLDPE), homogeneously branched linear ethylene / α-olefin copolymers (e.g., TAFMER™ from Mitsui Petrochemical Co., Ltd. and Exact TM Plastomers), homogeneously branched, substantially linear ethylene / α-olefin polymers (such as The Dow Chemical Company's AFFINITY™ polyolefin plastomers and ENGAGE™ polyolefin elastomers), and ethylene block copolymers (such as The Dow Chemical Company's INFUSE™).

[0019] The polar ethylene polymer A is polymerized from unsaturated alkyl ester and vinyl ester. The content of the structural unit derived from vinyl ester in the polar ethylene polymer A is 20 to 55 wt%, preferably 35 to 55 wt%.

[0020] The alkyl group in the unsaturated alkyl ester may be an alkyl group with 1 to 8 carbon atoms, preferably an alkyl group with 1 to 4 carbon atoms; the alkyl group may be substituted by trialkoxysilane. The unsaturated alkyl ester may be selected from one or more of alkyl acrylate and alkyl methacrylate.

[0021] The alkyl acrylate may be selected from at least one of ethyl acrylate, methyl acrylate, tert-butyl acrylate, n-butyl acrylate and 2-ethylhexyl acrylate, preferably methyl acrylate, ethyl acrylate and n-butyl acrylate or tert-butyl acrylate.

[0022] The alkyl methacrylate can be selected from lauryl methacrylate, myristyl methacrylate, palmitoyl methacrylate, octadecyl methacrylate, 3-methacryloylpropyltrimethoxysilane, 3-methacryloyloxy, cyclohexyl methacrylate, isodecyl methacrylate, 2-methoxyethyl methacrylate, tetrahydrofurfuryl methacrylate, octyl methacrylate, 2-phenoxyethyl methacrylate, isobornyl methacrylate, octyl methacrylate, isooctyl methacrylate, and oleyl methacrylate.

[0023] The vinyl ester may be a vinyl ester having 4 to 20 carbon atoms, preferably a vinyl ester having 4 to 7 carbon atoms; for example, it may be a carboxylic acid vinyl ester.

[0024] The carboxylic acid group in the vinyl carboxylate may have 2 to 8 carbon atoms, preferably 2 to 5 carbon atoms.

[0025] The vinyl carboxylate may be selected from one or more of vinyl acetate, vinyl butyrate, vinyl pivalate, vinyl neononanoate, vinyl neodecanoate and ethylene 2-ethylhexanoate; preferably vinyl acetate.

[0026] The modified carbon nanotubes are selected from one or more of organic silicon modified carbon nanotubes and polar ethylene polymer modified carbon nanotubes. The modified carbon nanotubes can be formed by grafting one of organic silicon and polar ethylene polymer B onto carbon nanotubes.

[0027] The carbon nanotubes can be any existing carbon nanotubes, and are preferably carbon nanotubes with a pure surface having completely sp2 hybridized hydrocarbon-carbon bonds.

[0028] The carbon nanotube (CNT) may be a multi-walled carbon nanotube (MWNT) or a single-walled carbon nanotube (SWNT). Since graphene nanoparticles and the carbon nanotube have the same chemical structure, the carbon nanotube (CNT) may also be a graphene nanoparticle.

[0029] The length of the carbon nanotubes can be selected within a wide range. As a preferred embodiment, the length of the carbon nanotubes is no more than 10 micrometers (μm), preferably no more than 5 μm, and more preferably no more than 2 μm.

[0030] The surface area of ​​the carbon nanotubes can be selected within a wide range. As a preferred embodiment, the surface area of ​​the carbon nanotubes should be greater than 150 m 2 / g, more preferably greater than 200m 2 / g.

[0031] As a specific solution, the carbon nanotubes can be selected from multi-walled carbon nanotubes purchased from Aldrich, NTP3003 (outer diameter 7-15nm) from Shenzhen Nanoport Co., Ltd., FT9000 (diameter 10-25nm) from Jiangsu Tiannai Technology Co., Ltd., graphene nanoparticles from XG Sciences, USA (Surface area is 500m 2 / g).

[0032] The organosilicon-modified carbon nanotube is preferably a POSS-modified carbon nanotube. The POSS-modified carbon nanotube is a carbon nanotube with cage-type polysilsesquioxane grafted on the surface.

[0033] The preparation method of the POSS modified carbon nanotubes can adopt an existing method. For example, reference can be made to X Chen, H. Shimizu, Polymer 2008, volume 49(4), Page 943-951; (https: / / doi.org / 10.1016 / j.polymer.2008.01.014).

[0034] According to an embodiment disclosed in the present invention, the method for preparing POSS-modified carbon nanotubes comprises: placing carbon nanotubes in HNO3 (4.5mol / L) for 40-60h, the reaction product is added into hydrogen peroxide, filtered and cleaned to obtain surface-modified HO-carbon nanotube-COOH without impurities; surface-modified HO-carbon nanotube-COOH and SOCl 2 The reaction obtains carbon nanotubes whose surfaces are modified by –COCl groups; the carbon nanotubes whose surfaces are modified by –COCl groups react with POSS to obtain POSS-modified carbon nanotubes.

[0035] Taking POSS and multi-walled carbon nanotubes (MWNT) as examples, the preparation mechanism of POSS-modified carbon nanotubes is as follows:

[0036]

[0037] in, Multi-walled carbon nanotubes (MWNT).

[0038] The polar ethylene polymer modified carbon nanotubes are carbon nanotubes with polar ethylene polymer B grafted on the surface.

[0039] The polar ethylene polymer B is polymerized from unsaturated alkyl ester and vinyl ester. The content of the structural unit derived from vinyl ester in the polar ethylene polymer B is 20 to 55 wt%, preferably 35 to 55 wt%.

[0040] The alkyl group in the unsaturated alkyl ester may be an alkyl group with 1 to 8 carbon atoms, preferably an alkyl group with 1 to 4 carbon atoms; the alkyl group may be substituted by trialkoxysilane. The unsaturated alkyl ester may be selected from one or more of alkyl acrylate and alkyl methacrylate.

[0041] The alkyl acrylate may be selected from at least one of ethyl acrylate, methyl acrylate, tert-butyl acrylate, n-butyl acrylate and 2-ethylhexyl acrylate, preferably methyl acrylate, ethyl acrylate and n-butyl acrylate or tert-butyl acrylate.

[0042] The alkyl methacrylate can be selected from lauryl methacrylate, myristyl methacrylate, palmitoyl methacrylate, octadecyl methacrylate, 3-methacryloylpropyltrimethoxysilane, 3-methacryloyloxy, cyclohexyl methacrylate, isodecyl methacrylate, 2-methoxyethyl methacrylate, tetrahydrofurfuryl methacrylate, octyl methacrylate, 2-phenoxyethyl methacrylate, isobornyl methacrylate, octyl methacrylate, isooctyl methacrylate, and oleyl methacrylate.

[0043] The vinyl ester may be a vinyl ester having 4 to 20 carbon atoms, preferably a vinyl ester having 4 to 7 carbon atoms; for example, it may be a carboxylic acid vinyl ester.

[0044] The carboxylic acid group in the vinyl carboxylate may have 2 to 8 carbon atoms, preferably 2 to 5 carbon atoms.

[0045] The vinyl carboxylate may be selected from one or more of vinyl acetate, vinyl butyrate, vinyl pivalate, vinyl neononanoate, vinyl neodecanoate and ethylene 2-ethylhexanoate; preferably vinyl acetate.

[0046] The selection range of the polar ethylene polymer A is the same as that of the polar ethylene polymer B. The polar ethylene polymer A and the polar ethylene polymer B may be the same or different.

[0047] The method for preparing the polar ethylene polymer modified carbon nanotubes can adopt the existing method.

[0048] According to an embodiment disclosed in the present invention, the method for preparing polar ethylene polymer modified carbon nanotubes comprises: placing carbon nanotubes in HNO 3 (4.5mol / L) for 40-60h (e.g., 48h), the reaction product is added to hydrogen peroxide, filtered, and cleaned to obtain surface-modified HO-carbon nanotube-COOH without impurities; hexadecylamine is added to the surface-modified HO-carbon nanotube-COOH, and the reaction is stirred at 120-220°C for 4-12h, the obtained product is washed with ethanol, filtered, and dried to obtain hexadecylamine-modified carbon nanotubes (HO-carbon nanotube-CONHC 16 H 33 ).

[0049] HO-CNT-CONHC 16 H 33 Ultrasonic dispersion in ethanol, addition of NaOH for 1-3 hours, then washing with ethanol and drying; the product is dispersed in xylene, polar ethylene polymer B is gradually added, and heating reaction is carried out for 3-8 hours; the product is precipitated in methanol, filtered, and then dried to obtain polar ethylene polymer modified carbon nanotubes.

[0050] Taking poly(ethylene-n-butylene-acrylate-co-glycidyl methacrylate) (EBA-GMA) and multi-walled carbon nanotubes (MWNT) as examples, the preparation mechanism of polar ethylene polymer modified carbon nanotubes is as follows:

[0051]

[0052] in, Multi-walled carbon nanotubes (MWNT).

[0053] The carbon black can be any existing carbon black, preferably acetylene black.

[0054] The primary particle size, oil absorption value (DBP), and 325 mesh residue of the carbon black can be selected within a wide range. As a preferred embodiment, the primary particle size of the carbon black is between 25 and 50 nm, the oil absorption value (DBP) is between 40 and 300 ml / 100 g, and the 325 mesh residue is ≤ 200 ppm. The carbon black particles of the carbon black product seen by the naked eye are generally aggregates. The primary particle size of the carbon black generally refers to the arithmetic mean of the primary particle size of a single carbon black or aggregate.

[0055] The oil absorption value (DBP), apparent density and iodine absorption value of the acetylene black can be selected in a wide range. As a preferred embodiment, the acetylene black has a DBP of 150-250 ml / 100 g, an apparent density of 0.8-2.5 g / cm 3 The apparent density of acetylene black is 200 ml / 100 g, and the iodine absorption value is 85 to 103 mg / g. More preferably, the acetylene black has a DBP of 200 ml / 100 g, a 3 Apparent density and iodine absorption value of 90-96 mg / g.

[0056] The oil absorption value DBP is measured according to “ASTM D2414: Standard Test Method for Oil Absorption Number (OAN) of Carbon Black”; and the iodine absorption value is measured according to “ASTM D1510-96: Standard Test Method for Iodine Absorption of Carbon Black”.

[0057] The peroxide can be selected from a wide range. As a preferred embodiment, the peroxide is selected from at least one of diisopropylbenzene peroxide and di-tert-butyl diisopropylbenzene peroxide;

[0058] The antioxidant can be selected in a wide range. As a preferred embodiment, the antioxidant is selected from one or more of 4,4'-thiobis(6-tert-butyl-3-methylphenol), tris[2,4-di-tert-butylphenyl]phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; for example, a mixed antioxidant prepared by mixing antioxidant 1010, antioxidant 168, and antioxidant 1024 in any mass ratio.

[0059] The second object of the present invention is to provide a method for preparing the polymer semiconductor shielding material described in the first object of the invention.

[0060] One of the purposes of the invention is that the method for preparing the polymer semiconductor shielding material can adopt any existing method for preparing a semiconductor shielding material.

[0061] According to an embodiment disclosed in the present invention, as a scheme, a method for preparing a semiconductor shielding material includes: preparing raw materials according to the components and amounts described in one of the purposes of the invention; mixing the raw materials except peroxide at 80-130°C for 3-12 minutes in an internal mixer, and after the obtained mixture is cooled, adding peroxide to completely absorb the oxide to obtain the polymer semiconductor shielding material.

[0062] A third object of the present invention is to provide a polymer semiconductor shielding layer.

[0063] A polymer semiconductor shielding layer is prepared from the polymer semiconductor shielding material described in one of the invention purposes or the polymer semiconductor shielding material prepared by the preparation method described in the second invention purpose.

[0064] The polymer semiconductor shielding layer can be prepared by using any existing method for preparing a semiconductor shielding layer.

[0065] Compared with the prior art, the present invention has the following beneficial effects:

[0066] Although adding unmodified carbon nanotubes or generally modified carbon nanotubes (such as CNTs simply grafted with hexadecyl) to the polymer semiconductor shielding material system can improve the conductive properties of the system, they cannot achieve the desired better surface compatibility and dispersibility, and have little contribution to surface smoothness, and some even reduce the surface smoothness.

[0067] Compared with unmodified carbon nanotubes or generally modified carbon nanotubes, the modified carbon nanotubes of the present invention are grafted with silicone and polar ethylene polymers on the surface. The silicone and polar ethylene polymer modified carbon nanotubes improve their dispersibility in the polymer semiconductor shielding material system and their compatibility with the resin surface; the carbon nanotubes modified with silicone and polar ethylene polymers can greatly reduce the viscosity of the polymer semiconductor shielding material system under high shear strength, thereby greatly improving the fluidity of the system, and finally obtaining an ultra-smooth cable shielding material.

[0068] Since silicone and polar ethylene polymer modified carbon nanotubes have strong conductivity, they can greatly reduce the amount of carbon black used in the polymer semiconductor shielding material system. It also reduces to a certain extent the problem of "protrusions are easily generated when the co-extrusion process is used to prepare the semiconductor shielding layer added with carbon black, resulting in reduced interface smoothness of the semiconductor shielding layer added with carbon black", and further improves the smoothness of the polymer semiconductor shielding material system.

[0069] The present invention adopts organic silicon and polar ethylene polymer modified carbon nanotubes to replace part of carbon black and add them into the polymer semiconductor shielding material system, which not only greatly reduces the volume resistance, but also greatly improves the surface smoothness, thereby obtaining a semi-conductive shielding material suitable for HV and EHV cable applications with both super smoothness and strong conductivity.

[0070] The present invention further adopts POSS to modify carbon nanotubes. POSS has a variety of three-dimensional inorganic cage structures, and can be connected to various organic functional groups on the side chain. In the present invention, the modification of carbon nanotubes by POSS is covalent bond modification; the present invention grafts POSS onto carbon nanotubes through covalent bonds, which can reduce the agglomeration between carbon nanotubes, increase the distance between carbon nanotubes, improve the compatibility and dispersibility of carbon nanotubes and resin systems, and has stable properties. Compared with non-covalent bond modification, POSS performs covalent bond modification on carbon nanotubes, the interaction force between POSS and carbon nanotubes is higher, and the stability of the modified substance obtained is better. DETAILED DESCRIPTION

[0071] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0072] Unless otherwise specified, the reagents used in the following examples and comparative examples are all commercially available products.

[0073] Example 1

[0074] (1) Preparation of POSS modified carbon nanotubes:

[0075] 20 g of multi-walled carbon nanotubes (MWNT) (model NC3100, purchased from Nanocyl) were placed in 2.0 L of HNO 3 (4.5mol / L) for 48h, then the reaction product was added into hydrogen peroxide, filtered and cleaned to obtain surface-modified HO-MWNT-COOH without impurities. 2 The reaction yielded MWNTs modified with surface-COCl groups. The MWNTs modified with surface-COCl groups reacted with 50 g of amino-containing POSS (model AM0265, purchased from Hybrid Plastics) to obtain POSS-modified carbon nanotubes. The POSS-modified carbon nanotubes contained approximately 19 g of pure MWNTs.

[0076] (2) Preparation of EBA-modified carbon nanotubes:

[0077] 20 g of multi-walled carbon nanotubes (MWNT) (model NC3100, purchased from Nanocyl) were placed in 2.0 L of HNO 3 (4.5mol / L) for 48h, then the reaction product was added to hydrogen peroxide, filtered, and cleaned to obtain surface-modified HO-MWNT-COOH without impurities. HO-MWNT-COOH was added with 100g of hexadecylamine, stirred and reacted at 180°C for 8h, and the obtained product was washed with ethanol, filtered, and dried to obtain hexadecylamine-modified MWNT (HO-MWNT-CONHC 16 H 33 ). HO-MWNT-CONHC 16 H 33 Contains approximately 19 g of pure MWNTs.

[0078] HO-MWNT-CONHC 16 H 33 Ultrasonic dispersion was performed in 500 mL of ethanol, 1 g of NaOH was added and stirred for 2 h, then washed with ethanol and dried; the obtained product was redispersed in 2 L of xylene, 50 g of GMA-EBA (Lotader AX8750 from ARKEMA) was gradually added, and the reaction was heated for 5 h; the obtained product was precipitated in methanol, filtered and dried to obtain EBA-modified carbon nanotubes. EBA-modified carbon nanotubes contain about 19 g of pure MWNT.

[0079] Example 2

[0080] Preparation of semiconductor shielding materials:

[0081] (1) Prepare raw materials:

[0082] Polar ethylene polymer EBA ( E1770, purchased from REPSOL) 33.2 g;

[0083] Non-polar ethylene polymer POE (ENGAGE TM 8402, purchased from Dow Chemical) 33.2 g;

[0084] Acetylene black (Denka black) 29g;

[0085] 2.1 g of POSS modified carbon nanotubes prepared in Example 1;

[0086] Peroxide DCP (diisopropylbenzene peroxide, purchased from Norion) 1.5 g;

[0087] 1 g of mixed antioxidant (the mass ratio of antioxidant 1010, antioxidant 168 and antioxidant 1024 is 2:1:1);

[0088] (2) Ethylene polymer EBA and POE, acetylene black, POSS modified carbon nanotubes prepared in Example 1 and mixed antioxidant are mixed in an internal mixer at 130° C. for 15 min. After the obtained mixture is cooled, peroxide DCP is added and absorbed in a post-absorption device for 3-5 h to obtain a semiconductor shielding material.

[0089] Example 3

[0090] Preparation of semiconductor shielding materials:

[0091] (1) Prepare raw materials:

[0092] Polar ethylene polymer EBA ( E1770, purchased from REPSOL) 33.2 g;

[0093] Non-polar ethylene polymer POE (ENGAGE TM 8402, purchased from Dow Chemical) 33.2 g;

[0094] Acetylene black (Denka black) 30g;

[0095] 1.1 g of POSS modified carbon nanotubes prepared in Example 1;

[0096] Peroxide DCP (diisopropylbenzene peroxide, purchased from Norion) 1.5 g;

[0097] 1 g of mixed antioxidant (the mass ratio of antioxidant 1010, antioxidant 168 and antioxidant 1024 is 2:1:1);

[0098] (2) Ethylene polymer EBA and POE, acetylene black, POSS modified carbon nanotubes prepared in Example 1 and mixed antioxidant are mixed in an internal mixer at 130° C. for 15 min. After the obtained mixture is cooled, peroxide DCP is added and absorbed in a post-absorption device for 3-5 h to obtain a semiconductor shielding material.

[0099] Example 4

[0100] Preparation of semiconductor shielding materials:

[0101] (1) Prepare raw materials:

[0102] Polar ethylene polymer EBA ( E1770, purchased from REPSOL) 33.2 g;

[0103] Non-polar ethylene polymer POE (ENGAGE TM 8402, purchased from Dow Chemical) 33.2 g;

[0104] Acetylene black (Denka black) 28g;

[0105] 3.1 g of POSS modified carbon nanotubes prepared in Example 1;

[0106] Peroxide DCP (diisopropylbenzene peroxide, purchased from Norion) 1.5 g;

[0107] 1 g of mixed antioxidant (the mass ratio of antioxidant 1010, antioxidant 168 and antioxidant 1024 is 2:1:1);

[0108] (2) Ethylene polymer EBA and POE, acetylene black, POSS modified carbon nanotubes prepared in Example 1 and mixed antioxidant are mixed in an internal mixer at 130° C. for 15 min. After the obtained mixture is cooled, peroxide DCP is added and absorbed in a post-absorption device for 3-5 h to obtain a semiconductor shielding material.

[0109] Example 5

[0110] Preparation of semi-conductive shielding materials:

[0111] (1) Prepare raw materials:

[0112] Polar ethylene polymer EBA ( E1770, purchased from REPSOL) 33.2 g;

[0113] Non-polar ethylene polymer POE (ENGAGE TM 8402, purchased from Dow Chemical) 33.2 g;

[0114] Acetylene black (Denka black) 29g;

[0115] 2.1 g of EBA-modified carbon nanotubes prepared in Example 1;

[0116] Peroxide DCP (diisopropylbenzene peroxide, purchased from Norion) 1.5 g;

[0117] 1 g of mixed antioxidant (the mass ratio of antioxidant 1010, antioxidant 168 and antioxidant 1024 is 2:1:1);

[0118] (2) Ethylene polymer EBA and POE, acetylene black, EBA-modified carbon nanotubes prepared in Example 1 and a mixed antioxidant are mixed in an internal mixer at 130° C. for 15 min. After the mixture is cooled, peroxide DCP is added and absorbed in a post-absorption device for 3-5 h to obtain a semiconductor shielding material.

[0119] Example 6

[0120] Preparation of organosilicon-modified carbon nanotubes:

[0121] 20 grams of multi-walled carbon nanotubes (MWNT) (model NC3100, purchased from Nanocyl) were placed in 2.0L HNO3 (4.5mol / L) for 48 hours, and then the reaction product was added to hydrogen peroxide, filtered, and cleaned to obtain surface-modified HO-MWNT-COOH without impurities. HO-MWNT-COOH and 100 grams of silane coupling agent KH570 were added to toluene solvent, ultrasonically dispersed, refluxed at 100°C for 6 hours, and KH570 modified carbon nanotubes were obtained after washing, filtering, and drying. KH570 modified carbon nanotubes contain about 19g of pure MWNT.

[0122] Preparation of semi-conductive shielding materials:

[0123] (1) Prepare raw materials:

[0124] Polar ethylene polymer EBA ( E1770, purchased from REPSOL) 33.2 g;

[0125] Non-polar ethylene polymer POE (ENGAGE TM 8402, purchased from Dow Chemical) 33.2 g;

[0126] Acetylene black (Denka black) 29g;

[0127] 2.1 g of KH570 modified carbon nanotubes prepared above;

[0128] Peroxide DCP (diisopropylbenzene peroxide, purchased from Norion) 1.5 g;

[0129] 1 g of mixed antioxidant (the mass ratio of antioxidant 1010, antioxidant 168 and antioxidant 1024 is 2:1:1);

[0130] (2) Ethylene polymer EBA and POE, acetylene black, the KH570 modified carbon nanotubes prepared above and a mixed antioxidant were mixed in an internal mixer at 130° C. for 15 min. After the mixture was cooled, peroxide DCP was added and absorbed in a post-absorption device for 3-5 h to obtain a semiconductor shielding material.

[0131] Comparative Example 1

[0132] Preparation of semiconductor shielding materials:

[0133] (1) Prepare raw materials:

[0134] Polar ethylene polymer EBA ( E1770, purchased from REPSOL) 33.2 g;

[0135] Non-polar ethylene polymer POE (ENGAGETM 8402, purchased from Dow Chemical) 33.2 g;

[0136] Acetylene black (Denka black) 29g;

[0137] 2.1 g of hexadecylamine-modified MWNT prepared in Example 1;

[0138] Peroxide DCP (diisopropylbenzene peroxide, purchased from Norion) 1.5 g;

[0139] 1 g of mixed antioxidant (the mass ratio of antioxidant 1010, antioxidant 168 and antioxidant 1024 is 1:1:1);

[0140] (2) The polar ethylene polymer EBA, acetylene black, the EBA-modified carbon nanotubes prepared in Example 1 and the mixed antioxidant were mixed in an internal mixer at 130° C. for 15 min. After the obtained mixture was cooled, peroxide DCP was added to obtain a semiconductor shielding material.

[0141] Comparative Example 2

[0142] Preparation of semiconductor shielding materials:

[0143] (1) Prepare raw materials:

[0144] Polar ethylene polymer EBA ( E1770, purchased from REPSOL) 66.4 g;

[0145] Acetylene black (Denka black) 29g;

[0146] Multi-walled carbon nanotubes (MWNT) (model NC3100, purchased from Nanocyl) 2.1 g;

[0147] Peroxide DCP (diisopropylbenzene peroxide, purchased from Norion) 1.5 g;

[0148] 1 g of mixed antioxidant (the mass ratio of antioxidant 1010, antioxidant 168 and antioxidant 1024 is 1:1:1);

[0149] (2) The polar ethylene polymer EBA, acetylene black, multi-walled carbon nanotubes and a mixed antioxidant were mixed in an internal mixer at 130° C. for 15 min. After the obtained mixture was cooled, peroxide DCP was added to obtain a semiconductor shielding material.

[0150] Comparative Example 3

[0151] Preparation of semiconductor shielding materials:

[0152] (1) Prepare raw materials:

[0153] Polar ethylene polymer EBA ( E1770, purchased from REPSOL) 60.5 g;

[0154] Acetylene black (Denka black) 37g;

[0155] Peroxide DCP (diisopropylbenzene peroxide, purchased from Norion) 1.5 g;

[0156] 1 g of mixed antioxidant (the mass ratio of antioxidant 1010, antioxidant 168 and antioxidant 1024 is 1:1:1);

[0157] (2) The polar ethylene polymer EBA, acetylene black, the EBA-modified carbon nanotubes prepared in Example 1 and the mixed antioxidant were mixed in an internal mixer at 130° C. for 15 min. After the obtained mixture was cooled, peroxide DCP was added to obtain a semiconductor shielding material.

[0158] Performance Testing

[0159] The volume resistance and surface smoothness of the semiconductor shielding materials prepared in Examples 2-5, ie, Comparative Examples 1-3, were tested.

[0160] (I) Measurement of volume resistivity

[0161] The volume resistance (R) of the semiconductor shielding material is measured using a volume resistance meter. The test method is carried out in accordance with GB / T3048.3-2007 standard.

[0162] The volume resistivity (ρ) formula is ρ=R·S / L (derived from the volume resistivity (R) formula R=ρ·L / S). Where, R: represents resistance; ρ: represents volume resistivity; L: represents resistor length; S: represents resistor cross-sectional area.

[0163] The volume resistivity of the semiconductor shielding materials prepared in Examples 2-5, i.e., Comparative Examples 1-3, is shown in Table 1.

[0164] (ii) Measurement of surface smoothness or defect density:

[0165] The semiconductor shielding material and the ultra-high voltage insulation material (HFDB4201-EHV, purchased from Dow Chemical) were cast together to form a co-extruded film, which was then cured at high temperature (180° C.) and co-extruded into a cast film (the cast film was used to simulate the cable shielding layer).

[0166] The extruded cast film was scanned with a 3D optical microscope for surface interface protrusions, and the defect density was measured and calculated. The defect height was classified from 30μm to 70μm, with each 10μm increment as one level, and the number of protrusions was reported as the defect density (number of defects / m 2 ).

[0167] The defect densities of the semiconductor shielding materials prepared in Examples 2-5, i.e., Comparative Examples 1-3, are shown in Table 1.

[0168] Table 1

[0169]

[0170] Table 1 shows that compared with Comparative Example 3, the volume resistivity of Comparative Example 2 is significantly reduced, but the total defect density of Comparative Example 2 is also significantly increased. The difference between Comparative Example 3 and Comparative Example 2 is that Comparative Example 3 does not add carbon nanotubes, while Comparative Example 2 adds carbon nanotubes. This shows that the addition of carbon nanotubes to the semiconductor shielding material effectively reduces the resistivity, but affects the dispersibility of the conductive medium, and not only fails to improve the surface smoothness of the semiconductor shielding material, but reduces its surface smoothness.

[0171] Table 1 shows that compared with Comparative Example 1, the volume resistivity (23°C) of the semiconductor shielding material of Example 2-6 is reduced by 16-49%, the volume resistivity (90°C) is reduced by 11-58%, the defect density of 30-39μm is reduced by 60-67%, the defect density of 40-49μm is reduced by 21-71%, the defect density of 50-59μm is reduced by -20-60%, and the defect density of 60-69μm is reduced by 0-100%, and the total defect density is significantly reduced. The difference between Example 2-6 and Comparative Example 1 is that the added modified carbon nanotubes are different. Example 2-6 adds organic silicon and polar ethylene polymer modified carbon nanotubes, and Comparative Example 1 adds hexadecyl modified carbon nanotubes. It shows that compared with the semiconductor shielding material added with hexadecyl modified carbon nanotubes, the semiconductor shielding material added with organic silicon and polar ethylene polymer modified carbon nanotubes not only greatly reduces the volume resistivity, but also greatly improves the surface smoothness.

[0172] Table 1 shows that, compared with Example 6, the volume resistivity (23°C) of Example 2 is reduced by 38%, the volume resistivity (90°C) is reduced by 53%, the defect density of 30-39μm is reduced by 16%, the defect density of 40-49μm is reduced by 64%, the defect density of 50-59μm is reduced by 67%, and the defect density of 60-69μm is reduced by 100%. The difference between Example 2 and Example 6 is that the added modified carbon nanotubes are different, Example 6 adds KH570 modified carbon nanotubes, and Example 2 adds POSS modified carbon nanotubes. It shows that, compared with the semiconductor shielding material added with other organosilicon modified carbon nanotubes, the semiconductor shielding material added with POSS modified carbon nanotubes can further reduce the volume resistivity and improve the surface smoothness.

Claims

1. A polymer semiconductor shielding material, characterized in that: The polymer semiconductor shielding material is prepared from raw materials comprising the following components; Taking the total amount of raw materials as 100%, the components and their contents are as follows: Ethylene polymer 40-80wt%, preferably 50-68wt%; Carbon black 10-40wt%, preferably 25-35wt%; 0.1-20wt% of modified carbon nanotubes, preferably 0.5-12wt%; Peroxide 0-5wt%, preferably 0.5-2wt%; Antioxidant 0-5wt%, preferably 0.1-1wt%.

2. The polymer semiconductor shielding material according to claim 1, characterized in that The ethylene polymer is selected from one or more of a non-polar ethylene polymer and a polar ethylene polymer A; preferably, the ethylene polymer consists of a non-polar ethylene polymer and a polar ethylene polymer A; wherein the content of the polar ethylene polymer A is 1 to 60 wt%, preferably 20 to 60 wt%, of the total weight of the ethylene polymer; or / and, The carbon black has a primary particle size of 25 to 50 nm, an oil absorption value of 40 to 300 ml / 100 g, and a 325 mesh sieve residue of ≤200 ppm, and is preferably acetylene black; The modified carbon nanotubes are selected from one or more of organic silicon modified carbon nanotubes and polar ethylene polymer modified carbon nanotubes; or / and, The peroxide is selected from dicumyl peroxide and / or di-tert-butyl dicumyl peroxide; or / and, The antioxidant is selected from one or more of 4,4'-thiobis(6-tert-butyl-3-methylphenol), tris[2,4-di-tert-butylphenyl]phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.

3. The polymer semiconductor shielding material according to claim 2, characterized in that The non-polar ethylene polymer is polymerized from ethylene, α-olefin and optional diene; wherein the content of the structural unit derived from α-olefin is 1-25wt%, preferably 5-20wt%, the content of the structural unit derived from the optional diene is greater than 0 and ≤10wt%, and the rest is the structural unit derived from ethylene; or / and, The polar ethylene polymer A is polymerized from unsaturated alkyl ester and vinyl ester; the content of the structural unit derived from vinyl ester is 20 to 55 wt%, preferably 35 to 55 wt%.

4. The polymer semiconductor shielding material according to claim 3, characterized in that The α-olefin is an α-olefin having 3 to 12 carbon atoms, preferably an α-olefin having 4 to 8 carbon atoms; or / and, The alkyl group in the unsaturated alkyl ester is an alkyl group with 1 to 8 carbon atoms or a trialkoxysilane, preferably an alkyl group with 1 to 4 carbon atoms or a trialkoxysilane, more preferably one or more selected from alkyl acrylates and alkyl methacrylates; or / and, The vinyl ester is a vinyl ester having 4 to 20 carbon atoms, preferably a vinyl ester having 4 to 7 carbon atoms, and more preferably a vinyl carboxylate; the carboxylic acid group in the vinyl carboxylate has 2 to 8 carbon atoms, preferably 2 to 5 carbon atoms.

5. The polymer semiconductor shielding material according to claim 4, characterized in that The alkyl acrylate is selected from at least one of ethyl acrylate, methyl acrylate, tert-butyl acrylate, n-butyl acrylate and 2-ethylhexyl acrylate; or / and The alkyl methacrylate may be selected from lauryl methacrylate, myristyl methacrylate, palmitoyl methacrylate, octadecyl methacrylate, 3-methacryloylpropyltrimethoxysilane, 3-methacryloyloxy, cyclohexyl methacrylate, isodecyl methacrylate, 2-methoxyethyl methacrylate, tetrahydrofurfuryl methacrylate, octyl methacrylate, 2-phenoxyethyl methacrylate, isobornyl methacrylate, octyl methacrylate, isooctyl methacrylate, oleyl methacrylate; or / and The vinyl carboxylate is selected from one or more of vinyl acetate, vinyl butyrate, vinyl pivalate, vinyl neononanoate, vinyl neodecanoate and ethylene 2-ethylhexanoate.

6. The polymer semiconductor shielding material according to claim 2, characterized in that The organosilicon-modified carbon nanotubes are POSS-modified carbon nanotubes; The POSS modified carbon nanotubes are carbon nanotubes with cage-type polysilsesquioxane grafted on the surface; or / and, The polar ethylene polymer modified carbon nanotubes are carbon nanotubes with polar ethylene polymer B grafted on the surface.

7. The polymer semiconductor shielding material according to any one of claims 6, characterized in that: The polar ethylene polymer B is polymerized from unsaturated alkyl ester and vinyl ester; the content of the structural unit derived from vinyl ester is 20 to 55 wt%, preferably 35 to 55 wt%. Preferably, The alkyl group in the unsaturated alkyl ester is an alkyl group with 1 to 8 carbon atoms or a trialkoxysilane, preferably an alkyl group with 1 to 4 carbon atoms or a trialkoxysilane, more preferably one or more selected from alkyl acrylates and alkyl methacrylates; or / and, The vinyl ester is a vinyl ester having 4 to 20 carbon atoms, preferably a vinyl ester having 4 to 7 carbon atoms, and more preferably a vinyl carboxylate; the carboxylic acid group in the vinyl carboxylate has 2 to 8 carbon atoms, preferably 2 to 5 carbon atoms; More preferably, The alkyl acrylate is selected from at least one of ethyl acrylate, methyl acrylate, tert-butyl acrylate, n-butyl acrylate and 2-ethylhexyl acrylate; or / and The alkyl methacrylate may be selected from lauryl methacrylate, myristyl methacrylate, palmitoyl methacrylate, octadecyl methacrylate, 3-methacryloylpropyltrimethoxysilane, 3-methacryloyloxy, cyclohexyl methacrylate, isodecyl methacrylate, 2-methoxyethyl methacrylate, tetrahydrofurfuryl methacrylate, octyl methacrylate, 2-phenoxyethyl methacrylate, isobornyl methacrylate, octyl methacrylate, isooctyl methacrylate, oleyl methacrylate; or / and The vinyl carboxylate is selected from one or more of vinyl acetate, vinyl butyrate, vinyl pivalate, vinyl neononanoate, vinyl neodecanoate and ethylene 2-ethylhexanoate.

8. The polymer semiconductor shielding material according to claim 6, characterized in that The carbon nanotube is a carbon nanotube having a pure surface with complete sp2 hybridized hydrocarbon-carbon bonds; or / and, The carbon nanotubes are multi-walled carbon nanotubes, single-walled carbon nanotubes or graphene nanoparticles; or / and, The length of the carbon nanotubes does not exceed 10 micrometers, preferably does not exceed 5 micrometers; or / and, The surface area of ​​the carbon nanotubes is greater than 150 m 2 / g, preferably greater than 200m 2 / g; or / and.

9. A method for preparing the polymer semiconductor shielding material according to claims 1-8, characterized in that: The preparation method comprises: preparing raw materials according to the components and dosages; mixing the raw materials except peroxide in an internal mixer at 80-130°C for 3-12 minutes, adding peroxide after the obtained mixture is cooled, so that the oxide is completely absorbed to obtain the polymer semiconductor shielding material.

10. A polymer semiconductor shielding layer, characterized in that: The polymer semiconductor shielding layer is prepared from the polymer semiconductor shielding material described in any one of claims 1 to 8 or the polymer semiconductor shielding material prepared by the preparation method described in claim 9.

Citation Information

Patent Citations

  • Method for making core-shell polyhedral oligomeric silsesquioxane (POSS) coated multi-walled carbon nanotube (MWNT)

    CN103173041A

  • Carbon nanometer tube semiconductor shielding material and preparation method thereof

    CN108395610A

  • Semi-conductive PVC shielding material for environment-friendly automobile wire and preparation method of semi-conductive PVC shielding material

    CN117986770A

  • Conjugate nanofiber

    JP2012041665A

  • Method of manufacturing thermoplastic resin electromagnetic waves shielding material containing carbon nanotubes

    KR1020140080842A

Cited By

  • Semi-conductive shielding material composition and application thereof, semi-conductive shielding material and preparation method and application thereof

    CN120118419A

  • Semiconductive shielding material composition and application, semiconductive shielding material and preparation method and application thereof

    CN120118419B

  • Shielding material composition, shielding material, preparation method of shielding material, shielding material and application of shielding material

    CN120271910A

  • Shielding material composition, shielding material and preparation method thereof, shielding material and application thereof

    CN120271910B

  • Semi-conductive shielding material for cable and preparation method of semi-conductive shielding material

    CN121136258A